Sorafenib combined with transarterial chemoembolization compared with sorafenib alone in advanced hepatocellular carcinoma (SELECT): a multicenter, phase 3, randomized, controlled trial - Yan Zhao; Wei Bai; Rong Ding; Nan You; Lin Zheng; Lei Li; Jianbin Wu; Peng Zhang; Wukui Huang; Hui Zhang; Yongjin Zhang; Diwen Zhu; et al. (The Lancet Regional Health. Western Pacific, 2025)
Background: Patients with advanced hepatocellular carcinoma have poor prognosis. We aimed to investigate the efficacy of sorafenib combined with transarterial chemoembolization in patients with advanced hepatocellular carcinoma. Method: SELECT was a randomized, multi-centre, controlled, phase 3 trial done at twelve centres in China. Eligible patients were aged 18 years or older and had advanced-stage hepatocellular carcinoma, Barcelona Clinic Liver Cancer stage C diseases, Child-Pugh class A liver disease, Eastern Cooperative Oncology Group (ECOG) performance statuses of 0 or 1. Participants were randomly assigned (1:1) with a computer-generated random sequence to sorafenib combined with transarterial chemoembolization or sorafenib alone. The primary endpoint was overall survival. Secondary endpoints were time to progression, tumor response rate, disease control rate and safety. Efficacy was analyzed in the intention-to-treat, per-protocol and as-treated populations. Safety outcomes were analyzed in the safety population. This trial is registered with ClinicalTrials.gov, number NCT01906216. Findings: Between September 7, 2013, and Dec 4, 2019, 199 patients were randomly assigned, 99 to the combination group and 100 to the sorafenib alone group. Protocol adherence was 86% (85 of 99 patients) in the combination group and 56% (56 of 100 patients) in the sorafenib alone group. The most common reason for discontinuation was disease progression (68 [69%] in the combination group and 80 [80%] in the sorafenib alone group). The median age was 55 years (IQR 46-63). 164 (82.4%) of 199 were male and 35 (17.6%) were female. At a median follow-up of 13.6 months (IQR 6.8-28.2), in the intention-to-treat population, median overall survival was 14.9 months (95%CI 10.5-19.3 months) in the combination group versus 11.9 months (95%CI 9.0-14.8 months) in the sorafenib alone group (HR 0.862 [95%CI 0.645-1.150]; P=0.312). Median time to progression survival was significantly longer in the combination group than the sorafenib alone group (10.0 months [95%CI 6.4-13.6 months] vs 5.9 months [95%CI 3.1-8.7 months]; HR 0.686 [95%CI 0.515-0.954]; P=0.016). In the per-protocol and as-treated analyses, both median overall survival and time to progression was significantly improved in the combination group compared with sorafenib alone group. Interpretation: In SELECT trial, sorafenib combined with TACE did not show overall survival benefit over sorafenib alone in intention-to-treat analysis; however, significantly longer overall survival benefit and improved time to progression was observed in both per-protocol and as-treated analyses.